Analysis on Physical Mechanism of Sound Generation inside Cavities Based on Acoustic Analogy Method - Yang, Dangguo; Li, Jianqiang; Liu, Jun; Zhang, Yi; Li, Yaohua (Scientific Research, 2013)
Analysis of coupling aerodynamics and acoustics are performed to investigate the self-sustained oscillation and aerodynamic noise in two-dimensional flow past a cavity with length to depth ratio of 2 at subsonic speeds. The large eddy simulation (LES) equations and integral formulation of Ffowcs-Williams and Hawings (FW-H) are solved for the cavity with same conditions as experiments. The obtained density-field agrees well with Krishnamurty’s experimental schlieren photograph, which simulates flow-field distributions and the direction of sound wave radiation. The simulated self-sustained oscillation modes inside the cavity agree with Rossiter’s and Heller’s predicated results, which indicate frequency characteristics are obtained. Moreover, the results indicate that the feedback mechanism that new shedding-vortexes induced by propagation of sound wave created by the impingement of the shedding-vortexes in the shear-layer and rear cavity face leads to self-sustained oscillation and high noise inside the cavity. The peak acoustic pressure occurs in the first oscillation mode and the most of sound energy focuses on the low-frequency region.
Keywords: Sound Pressure Frequency Spectrum; Sound Pressure Level; Aerodynamic Noise; Sound Generation; Physical Mechanism; Cavity